2015
DOI: 10.1109/lawp.2015.2423687
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Impact of Soil Conductivity on Underground Magneto-Inductive Channel

Abstract: This letter presents our experimental endeavor to characterize underground magneto-inductive channels. Specifically, a range of experiments are conducted in realistic underground environments, and the measurement data are compared with channel models established in prior publications. The channel model proposed in [1], which incorporates the impact of soil conductivity, is found in better agreement with the measurement data than models without soil conductivity included. It is therefore concluded that, soil co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Experiments have been conducted in the range of 0-20 S/m, whereas simulations using the CST numerical package have examined the variation of the mutual inductance over broad variations of all the relevant parameters. In addition, we have assessed the accuracy of a proposal in the literatures [18,22] that the skin effect expression for attenuation might provide a good estimate. We have found that this is indeed a too simplistic and crude approximation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments have been conducted in the range of 0-20 S/m, whereas simulations using the CST numerical package have examined the variation of the mutual inductance over broad variations of all the relevant parameters. In addition, we have assessed the accuracy of a proposal in the literatures [18,22] that the skin effect expression for attenuation might provide a good estimate. We have found that this is indeed a too simplistic and crude approximation.…”
Section: Discussionmentioning
confidence: 99%
“…This is far from a trivial question. In many publications, among which [18,22], it is suggested that it suffices to consider the path loss, i.e. the attenuation of the wave in the conducting medium, and that this decline can be accounted for by using the expression for the attenuation of a plane wave (PW) in a conductive half space.…”
Section: Variation Of the Magnetic Field And The Poynting Vectormentioning
confidence: 99%
See 1 more Smart Citation
“…Low frequency (LF) electromagnetic signals are less prone to multipath effect and provide good obstacle penetration in near field [1,2]. Low frequency communication, taking advantage of these features, is an alternative solution for through-the-earth (TTE) wireless applications, such as subsurface wireless data acquisition [3], underground localization [4,5] and magnetic resonance sounding [6].…”
Section: Introductionmentioning
confidence: 99%
“…Near-field electromagnetic (EM) interactions are used in various application areas such as magnetic induction (MI) communications [1], MI tomography [2,3] and wireless power transfer [4]. They are being increasingly employed in wireless underground sensor networks [5,6] for applications such as environmental monitoring (in soil [7] and water [8]), landslide inspection [9] and underground pipeline surveillance [10]. Traditional wireless sensor approaches are inhibited by the complex propagation media encountered (e.g.…”
Section: Introductionmentioning
confidence: 99%